1998
DOI: 10.1111/j.1346-8138.1998.tb02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Unilateral Axillary Paget's Disease

Abstract: We herein report two cases of unilateral axillary Paget's disease. Extramammary Paget's disease commonly occurs in the anogenital area. Unilateral axillary occurrence is relatively rare. One defect was reconstructed with a pedicled scapular flap, and the other was reconstructed with split-skin graft after excision of the tumor. No recurrence was seen in either patient three years postoperatively. However, although the patient who had been reconstructed with a pedicled flap recovered uneventfully, the other pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…We present here the first, to our knowledge, histologically confirmed case of a pigmented EMPD occurring in a male patient and in an axillary location. Only one previous report by Ohno et al described two cases of axillary EMPD, which had a brownish appearance on clinical examination; however, there is no histologic description of pigmented Paget cells or increased number of intraepidermal dendritic melanocytes 56 . All cases (including the current one) demonstrated intraepidermal Paget cells with abundant cytoplasm containing conspicuous melanin pigment.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We present here the first, to our knowledge, histologically confirmed case of a pigmented EMPD occurring in a male patient and in an axillary location. Only one previous report by Ohno et al described two cases of axillary EMPD, which had a brownish appearance on clinical examination; however, there is no histologic description of pigmented Paget cells or increased number of intraepidermal dendritic melanocytes 56 . All cases (including the current one) demonstrated intraepidermal Paget cells with abundant cytoplasm containing conspicuous melanin pigment.…”
Section: Discussionmentioning
confidence: 57%
“…Axillary location of EMPD is very rare. A review of the literature revealed only 23 cases reported so far, the majority in Japanese population 48–64 (Table 1). Of these, 10 cases had isolated axillary involvement, while 13 demonstrated simultaneous axillary and genital disease (the so‐called triple EMPD).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous EMPD of the axilla and anogenital region is not rare; however unilateral axillary occurrences are extremely uncommon 16. In our case, the patient was diagnosed with a single unilateral lesion in the right axilla and had not developed any evidence of disease in any other location.…”
Section: Discussionmentioning
confidence: 61%
“…The precise pathomechanism of diffuse cutaneous melanosis is still uncertain. One possibility under discussion is that growth factors (alpha melanocytestimulating hormone together with endothelin-1 and hepatocyte growth factor) stimulate the proliferation of normal and malignant melanocytes in the skin [6]. This would cause severe melanogenesis and diffuse pigmentation.…”
Section: Dear Editorsmentioning
confidence: 99%
“…In a recently published review article, only 23 EMP patients had axillary involvement, and in only 10 of these was the axilla alone affected [5]. Ohno and colleagues reported on the multifocal presentation of EMP in which there is often involvement of the axillary and genital regions [6]. Pigmentation of axillary EMP lesions is very rare; in such instances, the lesions must be differentiated from melanoma and Bowen disease [5].…”
Section: Extramammary Paget Disease Involving One Axillamentioning
confidence: 99%